Multiplicative fitness, rapid haplotype discovery, and fitness decay explain evolution of human MHC - Lobkovsky, Alexander E.; Levi, Lee; Wolf, Yuri I.; Maiers, Martin; Gragert, Loren; Alter, Idan; Louzoun, Yoram; Koonin, Eugene V. (Proceedings of the National Academy of Sciences - PNAS, 2019)
The major histocompatibility complex (MHC) is a central component of the vertebrate immune system and hence evolves in the regime of a host–pathogen evolutionary race. The MHC is associated with quantitative traits which directly affect fitness and are subject to selection pressure. The evolution of haplotypes at the MHC HLA (HLA) locus is generally thought to be governed by selection for increased diversity that is manifested in overdominance and/or negative frequency-dependent selection (FDS). However, recently, a model combining purifying selection on haplotypes and balancing selection on alleles has been proposed. We compare the predictions of several population dynamics models of haplotype frequency evolution to the distributions derived from 6.59-million-donor HLA typings from the National Marrow Donor Program registry. We show that models that combine a multiplicative fitness function, extremely high haplotype discovery rates, and exponential fitness decay over time produce the best fit to the data for most of the analyzed populations. In contrast, overdominance is not supported, and population substructure does not explain the observed haplotype frequencies. Furthermore, there is no evidence of negative FDS. Thus, multiplicative fitness, rapid haplotype discovery, and rapid fitness decay appear to be the major factors shaping the HLA haplotype frequency distribution in the human population.